Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas - Kundrata, Robin; Németh, Tamás (Zootaxa, 2019)
Penia Laporte, 1838 is the most species-rich genus in the click-beetle tribe Dimini. Penia is distributed in the Himalayas, East and South East Asia. In this paper, we describe P. mantillerii sp. nov. from northern Vietnam. This species is easily recognizable due to its elongate body and large window-like elytral punctures. The most morphologically similar species to P. mantillerii sp. nov. are P. costipennis Fleutiaux, 1936 and P. sucinea Schimmel, 2001, which also occur in northern Vietnam. Male pregenital segments and genitalia are figured for the first time for P. sucinea. An identification key to the Penia species from Vietnam and surroundings is provided.